Comparison of the Effect of Social Support and Peers on The Career Maturity of Vocational High School Students - Putra, Rico; Dianastiti, Yelma; Zulfakar Mohd Nawi, Mohd; Marwan Mujahid bin Syed A, Syed (Jurnal Pendidikan dan Profesi Keguruan, 2026)
Objective: This study aimed to analyze and compare the effects of social support and peer support on the career maturity of vocational high school students, with an emphasis on practical implications for vocational education. While previous research has examined these predictors independently, limited studies have comparatively assessed their relative contributions within technical vocational contexts, where students are expected to demonstrate clear work readiness upon graduation. Method: This study employed a quantitative approach with a descriptive correlational design. The population consisted of 210 eleventh- and twelfth-grade students in the Heavy Equipment Engineering Program at SMKN 2 Tulungagung. A sample of 140 students was selected using proportional random sampling. Data were collected through validated Likert-scale questionnaires measuring social support, peer support, and career maturity. Data were analyzed using descriptive statistics, prerequisite tests, simple regression, and multiple regression analysis with a significance level of 0.05. Results: The findings revealed that social support had a positive and significant effect on career maturity (B = 0.403; p < 0.001), explaining 15.7% of the variance. Peer support also showed a positive and significant effect (B = 0.181; p = 0.028), contributing 3.4%. Simultaneously, both variables accounted for 20% of the variance in career maturity. These results indicate that structured social support from families and schools plays a more substantial role than peer influence in strengthening students’ readiness to make realistic and responsible career decisions in vocational settings. Novelty: This study provides a comparative empirical analysis of the differential contributions of social and peer support within a technical vocational education context, offering evidence-based recommendations for designing structured, relationship-based career guidance programs aligned with workforce-oriented educational goals.